Late Paleozoic tectonics of Southern Central Asian orogenic belt: Evidence from magmatic rocks in the northern Alxa, Northwest China - Wang, Er-Teng; Zhai, Xin-Wei; Chen, Wan-Feng; Ma, Zhen; Wu, Lei; Guo, Zhi-Ang; Wang, Yun; Song, Gao-Rui; Wang, Jin-Rong (Frontiers in Earth Science, 2023)
Late Paleozoic magmatic rock outcrops are common in the northern Alxa, southern Central Asian Orogenic Belt (CAOB), which is a key area for understanding tectonic processes and defining the final closure time of the Paleo-Asian Ocean (PAO). We present zircon U‒Pb chronology and whole-rock geochemistry data for late Paleozoic magmatic rocks from the Yagan area of northern Alxa. This paper reveals two periods of magmatism: syenogranite (374.8 Ma) and bimodal intrusive rocks, which consist of gabbro (261.4 Ma), diabase (262.9 Ma) and biotite monzogranite (263.4 Ma). The syenogranite is high-K calc-alkaline and shows enrichments in Th, Zr, Hf and LREEs; depletions in Sr, Nb, Ta, and Ti; and low Mg# values (6.9-13.2); the syenogranite was derived from partial melting of the crust and has volcanic arc characteristics. The gabbro and diabase have similar geochemical characteristics, such as enrichments in Pb, Rb, Sr, Zr, and Hf and depletions in Nb, Ta, and Ti, with positive εHf(t) values (+0.9 - +2.7 and +2.6 - +3.6, respectively), indicating that they originated from partial melting of depleted mantle and experienced crustal contamination during magma emplacement. The biotite monzogranite shows depletions in Nb, Ta, and Ti and εNd (t) values of -2.6 - -2.4 and resulted from partial melting of the lower crust caused by asthenospheric underplating. The bimodal intrusive rocks formed in a postcollision extensional setting. Combined with previous data, we conclude that northern Alxa was an active continental margin during the late Devonian and that the final closure of the Yagan branch ocean of the PAO occurred prior to the middle Permian.